Cash-flow analysis of a wind turbine operator - Muhamad Razali N.M.; Hashim A.H. (2023)
The intermittent characteristics of wind energy seriously affect the reliability and output power of wind turbine generator (WTG). The paper outlines a method to evaluate the distribution of WTG operator's daily cash-flow by developing an algorithm based on Monte-Carlo technique. Two-parameter Weibull type probability density function (PDF) is used to model wind profile at two locations. WTG's output is obtained by using power curve while also considering the availability factor derived from the Forced Outage Rate (FOR). The daily cash-flows were obtained by calculating the difference between the revenues from sales of power at feed-in-tariff and the cost of energy. The paper contributes towards a better understanding of wind profile's effect on the expected energy production and the sensitivity of profit distribution to changes in feed-in tariff. 2009 IEEE.